Students' experiences of learning in undergraduate education in Sri Lanka - Wijesundera, Subhashinie D. K. (2011)
This thesis argues that to better understand student learning in undergraduate education, it is useful to focus not only on how students are affected by the context of learning but also how they act on the context to achieve their own valued outcomes. The thesis specifically explored the question of ‘how do students regulate their learning in relation to the contextual demands and their own valued outcomes?’